The personal characteristics of witnesses as the basis of choice of tactics of interrogation - Zharinov A.I. (Психология и право, 2017)
The article is devoted to studying of psychological features of persons influencing the choice of tactics of interrogation of witnesses. In this study 70 students took part with incomplete higher education between the ages of 18 to 21 years. The experimental group consisted of 35 people with type external locus of control, a control group – 35 people with type internal locus of control. Was conducted a multifaceted study of the individual and identified groups of people with hysteroid, schizoid and psychasthenic personal orientation, which were selected ten theory-based, efficient tactic, allowing to improve the effectiveness of testimony. According to the results the efficiency of testimony depends on the type of locus of control, when the person has a internal locus control efficiency response without the use of tactics is significantly higher than in subjects with external type of locus of control. Were given ecommendations to improve the effectiveness of testimony to persons with internal and external locus of control in the process of interrogation depending on the personal profile.